2018
DOI: 10.12659/msm.909995
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Acupuncture for Essential Hypertension: A Meta-Analysis

Abstract: BackgroundThe aim of this study was to assess the efficacy and safety of acupuncture therapy for patients with hypertension.Material/MethodsWe searched PubMed, Embase, the Cochrane Library, the Chinese Biomedical Literature Database, the Chinese National Knowledge Infrastructure, and the Wan-fang Data Database from inception through 29 April 2017. Randomized controlled trials investigating acupuncture therapy for hypertension were included. Review Manager 5.3 software was used for the data analysis.ResultsA to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 25 publications
1
57
0
1
Order By: Relevance
“…For patients with high blood pressure who refuse to take medicine or have low drug compliance, other effective methods of lowering blood pressure need to be found. It has been shown that acupuncture is an effective way to lower blood pressure [35,36]. As a non-invasive treatment, TEAS is similar to acupuncture in stimulating acupoints, and many clinical studies have shown the feasibility and safety of TEAS [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…For patients with high blood pressure who refuse to take medicine or have low drug compliance, other effective methods of lowering blood pressure need to be found. It has been shown that acupuncture is an effective way to lower blood pressure [35,36]. As a non-invasive treatment, TEAS is similar to acupuncture in stimulating acupoints, and many clinical studies have shown the feasibility and safety of TEAS [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, few determine that acupuncture alone can manage BP in hypertensive adults (Wang et al, 2013). Rather, the consensus is that acupuncture, when combined with pharmacological therapy, lowers BP than either treatment alone (Li et al, 2014; Zhao et al, 2015, 2019; Chen et al, 2018; Yang et al, 2018; Niu et al, 2019). Therefore, acupuncture may best be used as an adjunctive treatment for hypertension.…”
Section: Evidence Supporting Acupuncture As a Treatment Of Hypertensionmentioning
confidence: 99%
“…5,6 Several randomized controlled trials (RCTs) have shown acupuncture to be effective at lowering blood pressure in patients with hypertension, 7,8 and meta-analyses have suggested that acupuncture may be an excellent complementary therapy for hypertension. 9,10 Acupuncture has also been shown to be effective at reducing the risk of myocardial infarction and improving post-emergence recovery through mechanisms that promote the secretion of neurotransmitters in the central nervous system. 11,12 The effects of acupuncture on hypertension are known and the Korean national health insurance has covered acupuncture treatment for over 30 years; however, research using data from the Korean national cohort database on the effect of acupuncture on cardiovascular complications in hypertensive patients is limited.…”
Section: Introductionmentioning
confidence: 99%